Communication for Development : a Practical Handbook - Tuckey, John (London [England] : Bloomsbury Academic, 2022)
"Broadcasting is now an important part of the international aid effort, and as such communication for development has ambitious aims: to save lives, improve livelihoods and end corruption. In order to achieve this, specialist innovative production techniques and formats are required. This book provides a practical and thorough guide to the production of effective broadcasting for development. It covers four key areas of communication: humanitarian broadcasting in emergencies; distance learning; empowerment, good governance and human rights; broadcasting for behaviour and social change. Tuckey takes us through each stage from project design, to selecting and training a production team and developing formats, with key emphasis on the inclusion of local communities."--
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Human rights in mass media; Mass media; Humanitarian intervention; Mass media -- Social aspects; Electronic books